Comparison of Conjunctival Autograft Versus Bare Sclera Technique as Treatment Modalities for Primary Pterygium - Sohaib Afzal, Farah Qamar, Safeet Shahbaz Khan, Muhammad Ahmed, Shujah Ur Rehman, Rabbia Qammer, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Pterygium is a fibrovascular conjunctival growth within the palpebral fissure extending onto the corneal surface. Recurrence is a common post-op complication of pterygium excision surgery, with various rates depending on the techniques used for its excision. Objective: Comparison of conjunctival autograft versus bare sclera technique as treatment modalities for primary pterygium. Material & Methods: This study was done in the Department of Ophthalmology of tertiary care hospital. In a prospective randomized controlled trial a sample size of 102 eyes with primary pterygium were allocated into two equally sized groups (51 patients in each): Group A underwent pterygium excision by bare sclera method, Group B underwent pterygium excision followed by conjuctival autograft. Both groups were analyzed and compared, for recurrence and complications with a mean follow-up time of 3 months. Result: Pterygium recurrence was detected in 16 (31.37%) patients using bare sclera technique (group A) and in 4 (7.84%) patients using conjuctival autograft technique (group B), that reveal a statistically significant difference (p = 0.003) Conclusion: Both surgical techniques are effective for pterygium excision but there is a statistically significant difference (p = 0.003) of pterygium recurrence between both techinques. Pterygium excision with conjuctival autograft should opt for better results in terms of recurrence as well as other complications. Bare sclera technique can be opted for preserving conjunctiva in case of glaucoma or scaring but at the expense of pterygium recurrences. Keywords: Pterygium, conjunctival autograft technique, bare sclera, recurrence.